2010
DOI: 10.1007/978-3-642-13489-0_35
|View full text |Cite
|
Sign up to set email alerts
|

PossDL — A Possibilistic DL Reasoner for Uncertainty Reasoning and Inconsistency Handling

Abstract: Abstract. Uncertainty reasoning and inconsistency handling are two important problems that often occur in the applications of the Semantic Web. Possibilistic description logics provide a flexible framework for representing and reasoning with ontologies where uncertain and/or inconsistent information exists. Based on our previous work, we develop a possibilistic description logic reasoner. Our demo will illustrate functionalities of our reasoner for various reasoning tasks that possibilistic description logics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In this article, we justify such proposal and we develop a theory of OWL axiom testing against RDF facts based on possibility theory, whose output is a degree of possibility and necessity of an axiom, given the available evidence. Our proposal is coherent with a recently proposed possibilistic extension of description logics [17,18].…”
Section: Related Worksupporting
confidence: 72%
“…In this article, we justify such proposal and we develop a theory of OWL axiom testing against RDF facts based on possibility theory, whose output is a degree of possibility and necessity of an axiom, given the available evidence. Our proposal is coherent with a recently proposed possibilistic extension of description logics [17,18].…”
Section: Related Worksupporting
confidence: 72%
“…In order to model epistemic uncertainty, soft ontologies have been defined within the possibilistic framework [57,58], that deals with certainty and possibility degrees of truth. Possibilistic ontologies aim at modeling the epistemic uncertainty characterizing experts' subjective knowledge and evaluation of the certainty of this knowledge.…”
Section: Ontologies and Soft Ontologiesmentioning
confidence: 99%
“…Possibilistic ontologies aim at modeling the epistemic uncertainty characterizing experts' subjective knowledge and evaluation of the certainty of this knowledge. To this end, several possibilistic DL reasoners have been defined [57,58] which allows representation and reasoning on uncertain statements such as "It is possible that this trail is a climbing trail". To this end each concept, relationships and axiom is associated to a real value α in (0, 1] representing its certainty level.…”
Section: Ontologies and Soft Ontologiesmentioning
confidence: 99%
“…It has been shown that checking the consistency degree and several inference services can be done with classical DLs reasoning services through consistent sub-sets of the Possibilistic-DLs KB. An implementation of a reasoner called DL-Poss, has been provided in [13]. A deeper discussion on Possibilistic-DLs has been provided in [14].…”
Section: Introductionmentioning
confidence: 99%